Farmers’ participatory evaluation of pongamia seed cake as a plant nutrient source in integrated nutrient management - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Through a project on “Strengthening Capacity for Participatory Research and Development Project for South Asia” organized by CIP-UPWARD and funded by IDRC, the principles and learnings of PR&D are applied at ICRISAT by assessing the value of Pongamia oil seed cake as a source of organic plant nutrients  through  women’s  Self-Help Groups and farmers. This PR&D project is linked with the USAID Project on “Developing Community-based Water-Energy Services and Markets: A Pilot Project”.